Molecular phylogenetic reconstruction and localization of the (TTAGG)n telomeric repeats in the chromosomes of Acromyrmex striatus (Roger, 1863) suggests a lower ancestral karyotype for leafcutter ants (Hymenoptera) - Tássia Tatiane Pontes Pereira; Ana Caroline Coelho Corrêa dos Reis; Danon Clemes Cardoso; Maykon Passos Cristiano (Comparative Cytogenetics, 2018)
Chromosome counts and karyotype characterization have proved to be important features of a genome. Chromosome changes during the diversification of ants might play an important role, given the diversity and success of Formicidae. Comparative karyotype analyses on ants have enriched and helped ant systematics. Among leafcutter ants, two major chromosome counts have been described, one frequent in Atta Fabricius, 1804 (2n = 22 in all Atta spp. whose karyotype is known) and the other frequent in Acromyrmex Mayr, 1865 (2n = 38 in the majority of species whose karyotype is known). The main exception is Acromyrmex striatus (Roger, 1863), which harbors a diploid chromosome set of 22. Here we describe the use of fluorescence in situ hybridization (FISH) with telomeric probes with (TTAGG)6 repeats to describe the telomere composition of A. striatus and to recover potential interstitial non-telomeric signals that may reflect fusion events during the evolution of leafcutter lineage from 38 to 22 chromosomes. Further, we reconstruct the ancestral chromosome numbers of the leafcutter clade based on a recently proposed molecular phylogenetic hypothesis and phylogenomic tree. Distinct signals have been observed in both extremities on the telomere chromosomes of A. striatus. Non-telomeric signals have not been retrieved in our analysis. It could be supposed that the low-numbered karyotype indeed represents the ancestral chromosome number of leafcutters. The phylogenetic reconstruction also recovered a low chromosome number from the diverse approaches implemented, suggesting that n = 11 is the most likely ancestral karyotype of the leafcutter ants and is a plesiomorphic feature shared between A. striatus and Atta spp.